Immunobiotics for the Bovine Host: Their Interaction with Intestinal Epithelial Cells and Their Effect on Antiviral Immunity - Villena, Julio; Aso, Hisashi; Rutten, Victor P. M. G.; Takahashi, Hideki; van Eden, Willem; Kitazawa, Haruki (Frontiers in Immunology, 2018)
The scientific community has reported several cases of microbes that exhibit elevated rates of antibiotic resistance in different regions of the planet. Due to this emergence of antimicrobial resistant microorganisms, the use of antibiotics as promoters of livestock animals’ growth is being banned in most countries around the world. One of the challenges of agricultural immunology therefore is to find alternatives by modulating the immune system of animals in drug-independent safe food production systems. In this regard, in an effort to supplant antibiotics from bovine feeds, several alternatives were proposed including the use of immunomodulatory probiotics (immunobiotics). The purpose of this review is to provide an update of the status of the modulation of intestinal antiviral innate immunity of the bovine host by immunobiotics, and the beneficial impact of immunobiotics on viral infections, focused on intestinal epithelial cells. The results of our group, which demonstrate the capacity of immunobiotic strains to beneficially modulate Toll-like receptor 3-triggered immune responses in bovine intestinal epithelial cells and improve the resistance to viral infections, are highlighted. This review provides comprehensive information on the innate immune response of bovine intestinal epithelial cells against virus, which can be further investigated for the development of strategies aimed to improve defenses in the bovine host.